Comunidade de aprendizagem: feminismos nas narrativas das estudantes do Ensino Médio - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
This research sought to create a safe and welcoming learning community, based on bell hooks thinking. Feminist speeches have circulated more frequently in recent years, and with these speeches a new generation of women recognize this social, political and philosophical movement. However, feminism cannot be thought of as unique, but as a complex movement, which comes from different places and epistemologies. The proposed research question is how do high school students' narratives circulate in relation to feminism and its developments in a dialogue in a learning community? When problematizing the theme of feminism in the students' narratives, we emphasize that we are committed to a feminism of the right to life, good living and freedom. In this research, the general objective was to understand the feminist narratives of high school students and their developments throughout a learning community. Aspiring to achieve this objective, we have the following specific objectives: (Re)signify the students' narratives based on different feminist theoretical references; highlight different oppressions narrated by the students and hope from the students' narratives for other possible existences. Our theoretical and methodological path is based on feminist studies and bell hooks' theorizations. The narratives were produced through a learning community that is the central point of bell hooks' educational practice. The community meetings addressed topics such as autobiographical narratives, feminism, oppression and female solidarity. 10 girls participated in the community after school. During the analysis, narratives were identified that question gender inequality in the profession, in politics and at home; narratives of “good” or “bad” feminism; narratives that persist about women and care; Narratives that denounce oppression, violence, and control over the body; narratives that do not recognize violence and oppression; and women’s rights narratives. The learning community strengthened bonds between participants, promoted reflection by sharing stories and is a valuable way to teach critical thinking and challenge assumptions.
Keywords: Estudantes do Ensino Médio; Feminismos; Comunidades de aprendizagem; Estudos feministas; bell hooks; High school students; Feminisms; Learning communities; feminist studies; bell hooks; CNPQ::CIENCIAS HUMANAS::EDUCACAO